Is it worth preserving the uterus? unanticipated pathology in hysterectomy for pelvic organ prolapse (POP) - Pandey, Deeksha; Inukollu, Pranadeep Reddy; Shetty, Jyothi; Hebbar, Shripad; Pai, Muralidhar V.; Kumar, Pratap (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In recent years concept of uterine conservation has been increasing at the time of surgical management of pelvic organ prolapse (POP). This study was intended to assess the risk of premalignant and malignant uterine/endometrial, and cervical pathology at the time of hysterectomy-based POP procedures, to better understand the risks of uterine conservation in the surgical treatment of POP in Indian setup. Methods: Patients who had undergone vaginal hysterectomy for POP in last five years were identified by medical record tracking using ICD-9 codes. Case records then were reviewed to collect patient characteristics and the final histopathological diagnosis of the hysterectomy specimen. Cases with premalignant or malignant uterine/endometrial or cervical pathology recognized prior to surgery were excluded. Results: A total of 573 women who underwent vaginal hysterectomy and pelvic floor repair for the sole indication of POP were included. On analyzing the histopathological diagnosis of the specimen obtained during surgery in 57.1% of cases the findings were consistent with the changes seen in cases of POP. Only 5.9 % of cases had cervical or endometrial pathologies who would have required treatment/follow up in future if the uterus was left in situ. Conclusions: The risk of missing a malignant and premalignant cervical or uterine pathology in women presenting with uterine prolapse is low if appropriate preoperative workup has been done. Uterine preservation in surgical management of POP could be considered an option.